Inteligência ambiental no diagnóstico do daltonismo pelo enfermeiro - de Luna-López, María Concepción; Robles, Rosalba; Ochoa, Alberto; Flores Padilla, Luis; Cervera Gómez, Luis Ernesto; Trejo Franco, Juana (Paco Editorial, 2020)
https://www.researchgate.net/profile/Luis_Cervera-Gomez2/publication/343323063_Inteligencia_ambiental_no_diagnostico_do_daltonismo_pelo_enfermeiro/links/5f232dbb299bf1340494b61d/Inteligencia-ambiental-no-diagnostico-do-daltonismo-pelo-enfermeiro.pdf